Pedagogical Culture of a Teacher in the Context of Perfection of the Future Pedagogues’ Quality - Yashchuk, Inna (Pedagogical Discourse, 2013)
The constituents of development of pedagogical culture, which is part of common mankind culture of modern teacher in the context of development of humane pedagogics, in which are represented with the most plenitude the spiritual, financial values of education, and also methods of creative pedagogical activity, are considered in the article. The attention on practical experience of active development of pedagogical culture as for teachers so students of rector Khmel’nytsky humanitarian pedagogical institute of M.M.Darmanskyi (2000-2005), on understanding of essence of pedagogical culture of Sh.O.Amonashvili is concentrated. The features, approaches in relation to forming of pedagogical culture in modern higher educational pedagogical establishment are considered.